Sunday School Service Management in the Huria Kristen Indonesia Sipangan Bolon (Evaluation and Recommendations for Improving Sunday School Ministry) - Purba, Nora Desriani; Nainggolan, Diana (Jurnal Teologi Trinity, 2024)
HKI Sipangan Bolon is responsible for providing Christian religious education to children so that children can know God from childhood through Sunday School services. It has a big role in the process of children's faith growth and lays a strong foundation of faith. Sunday School have an impact on the growth of the church because children are the next generation of the church in the future. This research aims to evaluate the management of Sunday School services at HKI Sipangan Bolon to provide recommendations for improvements. The method used in the research is qualitative research with an analytical descriptive approach. Based on research, it was found that the Sunday School service at HKI Sipangan Bolon had not carried out management functions, namely planning, organizing, implementing and evaluating thoroughly. Referring to the research findings, the author provides recommendations for improving service management at HKI Sipangan Bolon.